Association of child weight with attendance at a healthy lifestyle service among women with obesity during pregnancy - Frankie J. Fair; Hora Soltani (Wiley, 2024)
Abstract Women with obesity during pregnancy are at increased risk of excessive gestational weight gain (GWG) and other maternal and infant adverse outcomes, which all potentially increase childhood obesity. This study explored infant weight outcomes for women with a body mass index (BMI) ≥ 35 kg/m² who were offered an antenatal healthy lifestyle service. A retrospective cohort study, including linking data from two separate health care Trusts, was undertaken. Data were collected from maternity records for women with a BMI ≥ 35 kg/m2 referred to an antenatal healthy lifestyle service from 2009 to 2015. The respective child's weight outcome data was additionally collected from health and National Child Measurement Programme records. Univariate logistic regression determined the odds of childhood overweight, obesity and severe obesity according to attendance at the antenatal healthy lifestyle service, GWG and sociodemographic characteristics. Factors significant (p < 0.05) within the univariate analysis were entered into multiple logistic regression models. Among women with a BMI ≥ 35 kg/m², 30.4% of their children were obese at school entry and 13.3% severely obese. Healthy lifestyle service attendance was not associated with childhood overweight or obesity at any point within the univariate analysis. At school age multiple regression analysis showed the odds of overweight and obesity increased with excessive GWG and the odds of obesity decreased with a parent in a professional occupation, additionally having a mother who smoked in pregnancy increased severe obesity. Women should be supported to optimise their BMI before pregnancy. Additionally, rather than exclusively focusing on changing an individual's behaviour, future interventions should consider external influences such as the woman's family, friends and sociodemographic background.